Anatomy of the lower respiratory tract in domestic birds, with emphasis on respiration. (17th December 2017) - Casteleyn, C.; Cornillie, P.; Van Cruchten, S.; Van den Broeck, W.; Van Ginneken, C.; Simoens, P.
Summary: This manuscript describes the anatomy of the lower respiratory tract in domestic bird species including the chicken and pigeon. The here described anatomical structures play a major role avian respiration, which is fundamentally different from respiration in mammals. During inspiration and expiration, a continuous caudocranial airflow is present within the tertiary bronchi of the Paleopulmo, while the Neopulmo, which is only present in phylogenetically recent species, is characterized by tidal respiration. Various anatomical structures and aerodynamic mechanisms have been described in an attempt to explain the proposed mechanism of respiration. The air sac system that is essential for avian respiration usually comprises an unpaired clavicular air sac and paired cervical, cranial and caudal thoracic, and abdominal air sacs. The latter are by far the larger and are interwoven with the abdominal organs.